Menopausal Impact on the Association Between Thyroid Dysfunction and Lipid Profiles: A Cross-Sectional Study - Han, Yutong; Wang, Chuyuan; Zhang, Lihui; Zhu, Jun; Zhu, Mei; Li, Yongze; Teng, Di; Teng, Weiping; Shan, Zhongyan (Frontiers in Endocrinology, 2022)
Background: Both dyslipidemia and thyroid dysfunction have a high prevalence rate and are important risk factors for cardiovascular diseases. However, the relationship between blood lipids and thyroid dysfunction is still controversial. This study aims to analyze the blood lipids in people with different thyroid functions. Methods: A total of 80937 adults were included in this population-based cross-sectional TIDE survey, which collected demographic and clinical data on thyroid function, blood lipid levels and other metabolic indicators. After screening, the final analysis included 10,747 participants, who were divided into hypothyroidism (n=311), subclinical hypothyroidism (n=5015), hyperthyroidism (n=203), subclinical hyperthyroidism (n=118) and control (n=5500) groups. The risk of dyslipidemia was analyzed by a logistic regression model and divided into groups of female menopausal. Results: After full adjustment, significant associations were found between hypothyroidism and hyperTG. Subclinical hypothyroidism was associated with a significantly higher risk of hyperTG and hyperLDL-C. Hyperthyroidism was significantly correlated with a reduced risk of hyperTC and hyperLDL-C but positively correlated with the risk of low HDL-C. There was no significant association between subclinical hyperthyroidism and blood lipids. Hypothyroidism increased the risk of hyperTG in both premenopausal and postmenopausal females. Subclinical hypothyroidism was significantly associated with increased hyperTG and low HDL-C in premenopausal females.Hyperthyroidism was significantly associated with a reduced risk of hyperTC and hyperLDL-C in premenopausal females and an increased risk of low HDL-C in postmenopausal female. Conclusion: Abnormal thyroid function has an important effect on blood lipids and is closely related to female menopause.